(untitled) (Indian Journal of Psychology & Education, 2017)
The aim of the present study was to analyze the effect of father’s absence on feeling of security-insecurity. A total of 360 students (180 male and 180 female) were selected through stratified random sampling. Out of these, 180 students of class 11&12, age range of 14-16 were selected from Army School and remaining 180 students pursuing Graduation and Masters, age range of 19-21 were selected from Meerut College, Meerut. Security-Insecurity Inventory by Tiwari and Singh (1975) was used to assess feeling of security-insecurity. The data were analyzed by employing three way ANOVA followed with Newman-Keules Test. The findings revealed that father’s absence and gender have a significant effect on feeling of security-insecurity. Students having complete absence of father have more feeling of insecurity in comparison to those who have partial absence of father and no absence of father. The findings were discussed in the light of available researches.